Development and preliminary assessment of a CRISPR–Cas12a-based multiplex detection of Mycobacterium tuberculosis complex - Xiao, Jing; Li, Jieqiong; Quan, Shuting; Wang, Yacui; Jiang, Guanglu; Wang, Yi; Huang, Hairong; Jiao, Weiwei; Shen, Adong (Frontiers in Bioengineering and Biotechnology, 2023)
Since the onset of the COVID-19 pandemic in 2020, global efforts towards tuberculosis (TB) control have encountered unprecedented challenges. There is an urgent demand for efficient and cost-effective diagnostic technologies for TB. Recent advancements in CRISPR-Cas technologies have improved our capacity to detect pathogens. The present study established a CRISPR-Cas12a-based multiplex detection (designated as MCMD) that simultaneously targets two conserved insertion sequences (IS6110 and IS1081) to detect Mycobacterium tuberculosis complex (MTBC). The MCMD integrated a graphene oxide-assisted multiplex recombinase polymerase amplification (RPA) assay with a Cas12a-based trans-cleavage assay identified with fluorescent or lateral flow biosensor (LFB). The process can be performed at a constant temperature of around 37°C and completed within 1 h. The limit of detection (LoD) was 4 copies μL -1 , and no cross-reaction was observed with non-MTBC bacteria strains. This MCMD showed 74.8% sensitivity and 100% specificity in clinical samples from 107 patients with pulmonary TB and 40 non-TB patients compared to Xpert MTB/RIF assay (63.6%, 100%). In this study, we have developed a straightforward, rapid, highly sensitive, specific, and costeffective assay for the multiplex detection of MTBC. Our assay showed superior diagnostic performance when compared to the widely used Xpert assay. The novel approach employed in this study makes a substantial contribution to the detection of strains with low or no copies of IS6110 and facilitates point-of-care (POC) testing for MTBC in resource-limited countries.